Musician's dystonia. Issue 4 (28th May 2015) - Sussman, Jon
Abstract : Musician's dystonia is a task-specific dystonia that usually affects the embouchure or the most active digits of the most active hand, and therefore differs between instruments. Since it is usually painless and intermittent, the diagnosis is often delayed and it is commonly misdiagnosed as being an overuse disorder or tendon pathology. It arises from pathological brain plasticity: physiological studies suggest that it is an exaggeration of brain changes that are required to achieve advanced musical skills. Its treatment often has limited success; however, musical retraining, botulinum toxin or rehabilitation based on modifying the aberrant plasticity may help.